2021
DOI: 10.1002/bit.27646
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized electrochemical biosensor based on whole‐cell for heavy metal ions detection in water

Abstract: The heavy metals pollution represents one of the important issues in the environmental field since it is involved in many pathologies from cancer, neurodegenerative, and metabolic diseases. We propose an innovative portable biosensor for the determination of traces of trivalent arsenic (As(III)) and bivalent mercury (Hg(II)) in water. The system implements a strategy combining two advanced sensing modules consisting in (a) a whole cell based on engineered Escherichia coli as selective sensing element towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Thus, these three fluorescent metal-sensing strains could be used to detect hazardous heavy metals at concentration ranges that could have practical uses. Most existing WBC developments need a complicated instrument for detecting fluorescence [ 21 ]. From the production process perspective, our colorimetric biosensor system is easier to use because of its simple and visible detection platform.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these three fluorescent metal-sensing strains could be used to detect hazardous heavy metals at concentration ranges that could have practical uses. Most existing WBC developments need a complicated instrument for detecting fluorescence [ 21 ]. From the production process perspective, our colorimetric biosensor system is easier to use because of its simple and visible detection platform.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-based biosensing systems were already applied to monitoring heavy metal pollution in water sources including "Cu 2+ '' pollution (using microbial fuel based-biosensor "Escherichia coli Rosetta genetically modified strain") with a LoD of 28 µM [92], contamination with As 3+ and Hg 2+ could be detected with a LOD of 20 µM and 0.498 µM, respectively using an electrochemical cell-based biosensor [93]. Moreover, using an E. coli-arsR/zntA strain with an insertion in arsAp::egfp cell-based biosensor was used to determinate the presence of Pb 2+ contamination with a LoD of 2.06 µM in water artificially contaminated samples [94], and for Cd 2+ contamination in environmental water samples, using a TOP10/pPcad-ind biosensor (E. coli genetically modified strain tolerant to cadmium) with a LOD of 0.049 μM and 0.024 μM of Cd 2+ of exposure in early exponential and lag phase respectively [95].…”
Section: Biosensing Technologies In Water Cell-based Techniquesmentioning
confidence: 99%
“…Many biomarkers including metal ions or posttranslational protein modifications are still neglected. Heavy metals have been analyzed by electrochemical biosensor from water in the work of Sciuto and coauthors (2020), copper from water samples was determined in the work of Cui and coauthors (2014), and iron from the water was tested in the work of Kamal and coauthors (2014) [83][84][85]. Glycan electrochemical biosensor for cancer diagnosis was presented in the work of Kveton and coauthors (2019), the electrochemical behavior of phosphotyrosine was observed in the work of Popa and Duculescu (2013), and dual-mode sensor using an electrolyte-insulator-semiconductor fieldeffect device coupled with nanoplasmonic effects was developed for protein phosphorylation detection in the work of Bhalla and coauthors (2015) [86][87][88].…”
Section: Perspectives In the Diagnosis Of Alzheimer's Diseasementioning
confidence: 99%